Immunisation status during biologic therapy for hidradenitis suppurativa and psoriasis - Stone, Corey; Sheriff, Tabrez; Liang, Yicong; Murrell, Dédée F. (JEADV clinical practice, 2023)
Background The use of biologic agents has significantly improved the quality of life for patients with chronic skin diseases, and many other autoinflammatory diseases, over the past two decades. Due to the immunosuppressive nature of biologic agents, patients on these treatments are at increased risk of infection. Compulsory serological testing and vaccine optimisation before commencing biologic therapy is not common practice, potentially leaving some of these patients exposed to vaccine‐preventable disease. Objectives Our real‐world data aims to assess if the use of biologic agents in patients with hidradenitis suppurativa and psoriasis leads to an accelerated loss of immunity to diseases commonly vaccinated against. Methods We present 77 patients with psoriasis and hidradenitis who underwent serological testing before and after commencing biologic treatment. Statistical analysis, using the Z‐test for differences between two populations, was used to determine if a significant number of patients lost immunity after commencing biologic therapy for the treatment of their skin disease. Results A significant number of our patients lost immunity, especially to Hepatitis B (p < 0.001) and Diphtheria (p < 0.001), whilst being treated with a biologic agent. Conclusions Whilst no control group was included in this real‐world study, our findings suggest that biologic agents may shorten the longevity of vaccine‐induced immunity and calls for future, larger‐scale, prospective studies. We recommend pre‐biologic serology testing and vaccine optimisation to reduce the risk of vaccine‐preventable illnesses and unnecessary treatment interruptions.